Erectile dysfunction in fit and healthy young men: psychological or pathological? - Rastrelli, Giulia; Maggi, Mario (Translational Andrology and Urology, 2016)
Epidemiological studies consistently show that prevalence of erectile dysfunction (ED) increases with ageing. Nonetheless, complaints of ED even in younger men are becoming more and more frequent. Healthcare professionals working in Sexual Medicine but even those operating in different clinical contexts might be adequately prepared to answer this increasing requirement. ED in younger men is likely to be overlooked and dismissed without performing any medical assessment, even the most basic ones, such as collection of medical history and physical exam. This is due to the widespread assumption that ED in younger individuals is a self-limiting condition, which does not deserve any clinical evaluation or therapy and can be managed only with patient reassurance. However, evidence shows that, in younger subjects, organic, psychological and relational conditions can contribute to the pathogenesis of ED and all these conditions might be evaluated and treated, whenever necessary. Among the organic conditions contributing to the onset of ED, metabolic and cardiovascular (CV) risk factors are surprisingly of particular relevance in this age group. In fact, in younger men with ED, even more than in older ones, recognizing CV risk factors or conditions suggestive of cardio-metabolic derangements can help identifying men who, although at low absolute risk due to young age, carry a high relative risk for development of CV events. In this view, the assessment of a possible organic component of ED even in younger individuals acquires a pivotal importance, because it offers the unique opportunity to unearth the presence of CV risk factors, thus allowing effective and high quality preventive interventions.